Detection of Antibacterial Activity of Garlic Against Acinetobacter Species Isolated from Patients in Tertiary Care Hospital - Rao, Sareena; Naik, Deepashri (Journal of Natural Remedies, 2023)
The aim of the present study evaluates the antibacterial activity of garlic extracts on isolates of Acinetobacter. A total of 100 strains were collected from various samples at MGM hospital in Kamothe, Navi Mumbai. The susceptibilities of isolates to different antibiotics were tested by using the Kirby Bauer agar disk diffusion method. Seventy-nine per cent of isolated strains showed resistance to at least 14 or more antibiotics and all strains are multidrug resistant. Antibacterial activity of different concentrations of Garlic Extract was measured by well diffusion and the disk diffusion method. Garlic extract was used in the range of 5% to 100%. The present study suggests that multidrug-resistant Acinetobacter bacteria with significant antibiotic resistance show significant susceptibility to modest amounts of garlic extracts.